Dynamics of a microcapillary discharge plasma using a soft x-ray laser backlighter - Marconi, M.C. (2000)
We have used the new technique of soft x-ray laser shadowgraphy in combination with traditional plasma emission spectroscopy and theoretical modeling to study the dynamics of a plasma column created by a discharge through a 380 μm diameter evacuated microcapillary. The transient microcapillary plasma was imaged with high-spatial and temporal resolution using a tabletop discharge pumped 46.9-nm laser backlighter. Model computations show that the sharp boundary observed between the absorbent and transparent regions of the shadowgrams is defined by the spatial distribution of weakly ionized ions that are strongly photoionized by the probe laser. The plasma was observed to rapidly evolve from an initially nonuniform distribution into a column with good azimuthal symmetry and minimum density on axis [computed electron density on axis ne =(1-3)×1019 cm-3]. This concave electron density profile constitutes a plasma waveguide for laser radiation. Heated solely by Joule dissipation from relatively small excitation currents (1.5 kA), this dense plasma reaches substantial electron temperatures of Te=15-20 eV as a result of the absence of significant hydrodynamic losses and reduced radiation losses caused by large spectral line opacities. The results illustrate the potential of tabletop soft x-ray lasers as a new plasma diagnostic tool. ©2000 The American Physical Society.